The Effect of E-Filling Implementation and Tax Sanctions Implementation on Individual Taxpayer Compliance with Digital Literacy As A Moderating Variable - Suherman, Ruben; Ramadhan, Yanuar (Dinasti Publisher, 2025)
This study aims to analyze the influence of E-Filing and tax sanctions on individual taxpayer compliance, with digital literacy as a moderating variable, at KPP Pratama Tigaraksa. The population consists of 5,412 taxpayers, with a sample size of 100 respondents. The research employs a quantitative approach, and data analysis is conducted using Smart PLS 4 software. The results indicate that E-Filing (X1) does not have a significant effect on taxpayer compliance (Y), with a p-value of 0.178 (greater than 0.05) and a t-statistic of 1.347 (less than the t-Table value of 1.984). The regression coefficient of -0.131 indicates that an increase in E-Filing is associated with a decrease in taxpayer compliance. Conversely, tax sanctions (X2) significantly influence taxpayer compliance, with a p-value of 0.005 (less than 0.05) and a t-statistic of 2.802 (greater than the t-Table value of 1.984). The regression coefficient of 0.243 suggests that stricter tax sanctions improve taxpayer compliance. Digital literacy (Z) was found to be a significant moderator in the relationship between E-Filing and taxpayer compliance, with a moderation coefficient of 0.264, a t-statistic of 2.539, and a p-value of 0.011. However, digital literacy does not significantly moderate the relationship between tax sanctions and taxpayer compliance, as indicated by a moderation coefficient of 0.076, a t-statistic of 0.817, and a p-value of 0.414. These findings highlight the importance of digital literacy in enhancing the effectiveness of E-Filing, while tax sanctions remain a dominant factor in driving individual taxpayer compliance at KPP Pratama Tigaraksa